Hermetische Körper - Elena Fabietti (Recherches Germaniques)
The work of Gustav Meyrink (1868-1932) can be defined by a life-long engagement with a great number of esoteric movements of his age, from Theosophy through Christian mysticism, then diverse ascetic and ecstatic practices to Indian Yoga. In this paper, I show how Meyrink’s Occultism and his literary praxis are involved in a productive reciprocal exchange that can serve more broadly as a paradigmatic example of a modernist “naturalization of art” within the constellation of “occulture” around 1900. Meyrink’s artistic praxis reverses the traditional relation between art and nature: his literary production is not just inspired by Esotericism and its themes but constitutes one of the many bodily and ritual practices that characterize his engagement with the culture of Esotericism.